2009
DOI: 10.1021/ol902353t
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic Effect of Solvent Hydrogen Bond Basicity on the Regiochemistry of SNAr Reactions of Electron-Deficient Polyfluoroarenes

Abstract: It was found that solvent hydrogen bond basicity (SHBB) significantly affects the regiochemistry of the S(N)Ar reaction between secondary amines and activated polyfluoroarenes. A plausible mechanism involving a six-membered transition state is invoked for the formation of an ortho-substituted isomer, which is likely organized by a hydrogen bond. Evidence for this hypothesis is presented, and a regioselective amination reaction of activated polyfluoroarenes has been developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 21 publications
0
30
0
2
Order By: Relevance
“…[20] Recent kinetic or solvent studies support the hydrogen-bond (HB) hypothesis, without rigorously demonstrating it. [21][22][23][24][25] The computational study presented here allows us to rationalize all these experimental results.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…[20] Recent kinetic or solvent studies support the hydrogen-bond (HB) hypothesis, without rigorously demonstrating it. [21][22][23][24][25] The computational study presented here allows us to rationalize all these experimental results.…”
Section: Introductionmentioning
confidence: 75%
“…As the gas phase is very similar to apolar solvents, this explains the reported data from the literature. [11,24] The addition of methylamine to 2,4-dichloronitrobenzene always proceeds in a single step. The TS energies are 11.3 and 15.1 kcal mol À1 , respectively, for the ortho and the para substitution in methanol, and 13.0 and 22.6 kcal mol À1 in the gas phase.…”
Section: Resultsmentioning
confidence: 99%
“…44 They could not predict the experimentally observed rate increase in going from protic to dipolar aprotic solvents by using DFT/ PCM calculations, but QM/MM Monte Carlo simulations gave useful results. 44 In another paper, Wang and co-workers reported that the regiochemistry of the S N Ar reaction between secondary amines and different electron-deficient difluoroarenes was highly affected by the hydrogen bond basicity of the Reaction of (3 in Figure 1) Reaction of (8 in Figure 1) with dimethylamine j 45 Including these types of effects in regioisomeric predictions is obviously beyond the capabilities of PCM.…”
Section: Neutral Nucleophiles and Hf As Leaving Groupmentioning
confidence: 99%
“…In support of this, entropy of activation for the ortho-isomer is less negative than that for the para-isomer ( 228 it would not explain why this favourable interaction cannot occur with 2-NAB. The generation of negative charge on the nitro group oxygens in the σ-adduct formed from 4-NFB requires solvation and restriction of solvent molecules giving rise to a slightly more negative entropy of activation.…”
mentioning
confidence: 94%